Outcomes in diabetic patients treated with SGLT2-Inhibitors with acute myocardial infarction undergoing PCI: The SGLT2-I AMI PROTECT Registry - Paolisso, Pasquale; Bergamaschi, Luca; Gragnano, Felice; Gallinoro, Emanuele; Cesaro, Arturo; Sardu, Celestino; Mileva, Niya; Foà, Alberto; Armillotta, Matteo; Sansonetti, Angelo; Amicone, Sara; Impellizzeri, Andrea; et al. (Pharmacological research, 2023)
To investigate in-hospital and long-term prognosis in T2DM patients presenting with acute myocardial infarction (AMI) treated with SGLT2-I versus other oral anti-diabetic agents (non-SGLT2-I users). In this multicenter international registry all consecutive diabetic AMI patients undergoing percutaneous coronary intervention between 2018 and 2021 were enrolled and, based on the admission anti-diabetic therapy, divided into SGLT-I users versus non-SGLT2-I users. The primary endpoint was defined as a composite of cardiovascular death, recurrent AMI, and hospitalization for HF (MACE). Secondary outcomes included i) in-hospital cardiovascular death, recurrent AMI, occurrence of arrhythmias, and contrast-induced acute kidney injury (CI-AKI); ii) long-term cardiovascular mortality, recurrent AMI, heart failure (HF) hospitalization. The study population consisted of 646 AMI patients (with or without ST-segment elevation): 111 SGLT2-I users and 535 non-SGLT-I users. The use of SGLT2-I was associated with a significantly lower in-hospital cardiovascular death, arrhythmic burden, and occurrence of CI-AKI (all p < 0.05). During a median follow-up of 24 ± 13 months, the primary composite endpoint, as well as cardiovascular mortality and HF hospitalization were lower for SGLT2-I users compared to non-SGLT2-I patients (p < 0.04 for all). After adjusting for confounding factors, the use of SGLT2-I was identified as independent predictor of reduced MACE occurrence (HR=0.57; 95%CI:0.33–0.99; p = 0.039) and HF hospitalization (HR=0.46; 95%CI:0.21–0.98; p = 0.041). In T2DM AMI patients, the use of SGLT2-I was associated with a lower risk of adverse cardiovascular outcomes during index hospitalization and long-term follow-up. Our findings provide new insights into the cardioprotective effects of SGLT2-I in the setting of AMI. Data are part of the observational international registry: SGLT2-I AMI PROTECT. ClinicalTrials.gov Identifier: NCT05261867. [Display omitted] •Multicenter international registry of diabetic AMI patients undergoing PCI divided into SGLT-I users versus non-SGLT2-I users.•A mitigated negative LV remodeling was detected in patients treated with SGLT2-I.•SGLT2-I were associated with a lower in-hospital cardiovascular death and arrhythmic burden.•In SGLT2-I users cardiovascular mortality, HF hospitalization and MACE were significantly lower compared to no-SGLT2-I patients.